Design And Development Of Smart Autonomous Fire Detector Robot - Ab Hadi, Nik Azran (Medwell Journals, 2017)
Now a days, in industrial, commercial and domestic world, automation assumes an essential part. It is really a planning of various components so as to control, sense, regulate and instruct itself to accomplish a wanted result. This study purposely designed to develop a smart multiple sensor based fire fighting robot in our everyday life. So, a smart autonomous fire detector which deflects obstacle on pathway will be created with an extinguisher and some other important elements which controlled by a microcontroller. The system is cost effective has an extensive use. It can present effectively and good outcome during execution. It can be utilized purposely in commercial, domestic sectors and industrial uses which the condition of automatic job needed. If any fire detected, it will extinguish the fire using a water pump that gives to it. This system also able to avoid obstacles on its pathway by changing its direction of movement. This method is possible with the use of ultrasonic sensors. After extinguishing the fire it will move back to find another any presence of fire. It voluntarily senses and extinguishes fire without human guidance. This is mean to simulate the actual world process of robot executing a fire extinguishing task.